ANALISIS PENGARUH LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN, REPUTASI KAP TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (Pada Perusahaan Manufaktur Yang Terdaftar di BEI Indonesia Periode 2015- 2017) - Yus Fanila Puspa Arum, 15.05.52.0225; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2019)
This study aims to test and analyze empirically the effect of Liquidity, Profitability, Firm Size, KAP's Reputation on Timeliness of Financial Reporting. The object of this research is manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) for the period 2015-2017. The population in this study are a number of manufacturing companies listed on the Indonesia Stock Exchange (BEl) for the period 2015-2017. The sampling technique in this study was purposive sampling, namely sampling based on criteria. The criteria used are companies listed on the IDX in a period of 2015- 2017. Companies that use rupiah in delivering financial statements. Companies that have positive profits in a row for the period 2015-2017. Have complete data in accordance with this research. The data analysis technique uses logistic regression analysis. The results of the study show that liquidity has a positive effect on the timeliness of financial reporting. Profitability does not affect the timeliness offinancial reporting. Company size does not affect the timeliness of financial reporting. KAP's reputation does not affect the timeliness of financial reporting.